Difference between revisions of "2021 AMC 12B Problems/Problem 18"
Sugar rush (talk | contribs) |
(→Solution 6) |
||
(17 intermediate revisions by 6 users not shown) | |||
Line 6: | Line 6: | ||
==Solution 1== | ==Solution 1== | ||
Using the fact <math>z\bar{z}=|z|^2</math>, the equation rewrites itself as | Using the fact <math>z\bar{z}=|z|^2</math>, the equation rewrites itself as | ||
− | + | <cmath>\begin{align*} | |
− | <cmath>12z\bar{z}=2(z+2)(\bar{z}+2)+(z^2+1)(\bar{z}^2+1)+31 | + | 12z\bar{z}&=2(z+2)(\bar{z}+2)+(z^2+1)(\bar{z}^2+1)+31 \\ |
− | + | -12z\bar{z}+2z\bar{z}+4(z+\bar{z})+8+z^2\bar{z}^2+(z^2+\bar{z}^2)+32&=0 \\ | |
− | + | \left((z^2+2z\bar{z}+\bar{z}^2)+4(z+\bar{z})+4\right)+\left(z^2\bar{z}^2-12z\bar{z}+36\right)&=0 \\ | |
− | + | (z+\bar{z}+2)^2+(z\bar{z}-6)^2&=0. | |
+ | \end{align*}</cmath> | ||
As the two quantities in the parentheses are real, both quantities must equal <math>0</math> so <cmath>z+\frac6z=z+\bar{z}=\boxed{\textbf{(A) }-2}.</cmath> | As the two quantities in the parentheses are real, both quantities must equal <math>0</math> so <cmath>z+\frac6z=z+\bar{z}=\boxed{\textbf{(A) }-2}.</cmath> | ||
==Solution 2== | ==Solution 2== | ||
− | + | ||
+ | Let <math>z = a + bi</math>, <math>z^2 = a^2-b^2+2abi</math> | ||
+ | |||
+ | By the equation given in the problem | ||
+ | |||
+ | <cmath>12(a^2+b^2) = 2((a+2)^2 + b^2) + ((a^2-b^2+1)^2 + (2ab)^2) + 31</cmath> | ||
+ | |||
+ | <cmath>12a^2 + 12b^2 = 2a^2 + 8a + 8 + 2b^2 + a^4 + b^4 + 1 + 2a^2 - 2b^2 - 2a^2b^2 + 4a^2b^2 + 31</cmath> | ||
+ | |||
+ | <cmath>a^4 + b^4 - 8a^2 - 12b^2 + 2a^2b^2 + 8a + 40 = 0</cmath> | ||
+ | |||
+ | <cmath>(a^2+b^2)^2 - 12(a^2+b^2) + 4(a^2 + 2a + 1) + 36=0</cmath> | ||
+ | |||
+ | <cmath>(a^2 + b^2 - 6)^2 + 4(a+1)^2 = 0</cmath> | ||
+ | |||
+ | Therefore, <math>a^2 + b^2 - 6 = 0</math> and <math>a+1 = 0</math> | ||
+ | |||
+ | <math>a = -1</math>, <math>b^2 = 6-1 = 5</math>, <math>b = \sqrt{5}</math> | ||
+ | |||
+ | <cmath>z + \frac{6}{z} = \frac{ a^2 - b^2 + 6 + 2abi }{ a+bi } = \frac{ 1 - 5 + 6 + 2(-1)\sqrt{5} i }{ -1 + i \sqrt{5} } = \frac{ 2 - 2i \sqrt{5} }{-1 + i \sqrt{5}} = \boxed{\textbf{(A)} -2}</cmath> | ||
+ | |||
+ | ~[https://artofproblemsolving.com/wiki/index.php/User:Isabelchen isabelchen] | ||
==Solution 3== | ==Solution 3== | ||
Line 20: | Line 42: | ||
<cmath> |z|^2 = 6</cmath> | <cmath> |z|^2 = 6</cmath> | ||
<cmath> |z+2|^2 = (\frac{x}{2} + 2)^2 + \frac{24-x^2}{4} = 2x+10</cmath> | <cmath> |z+2|^2 = (\frac{x}{2} + 2)^2 + \frac{24-x^2}{4} = 2x+10</cmath> | ||
− | <cmath> |z^2+1|^2 = |xz -6 +1|^2 = (\frac{x^2}{2}-5)^2 + \frac{x^2(24-x^2)}{4} = x^2 +25</cmath> | + | <cmath> |z^2+1|^2 = |xz -6 +1|^2 = \left(\frac{x^2}{2}-5\right)^2 + \frac{x^2(24-x^2)}{4} = x^2 +25</cmath> |
Plugging the above back to the original equation, we have | Plugging the above back to the original equation, we have | ||
<cmath> 12*6 = 2(2x+10) + x^2 + 25 + 31</cmath> | <cmath> 12*6 = 2(2x+10) + x^2 + 25 + 31</cmath> | ||
Line 28: | Line 50: | ||
~Sequoia | ~Sequoia | ||
− | ==Solution 4 ( | + | ==Solution 4 (Funny Observations)== |
There are actually several ways to see that <math>|z|^2 = 6.</math> I present two troll ways of seeing it, and a legitimate way of checking. | There are actually several ways to see that <math>|z|^2 = 6.</math> I present two troll ways of seeing it, and a legitimate way of checking. | ||
Line 46: | Line 68: | ||
Let <math>a = w + \overline{w} \in \mathbb{R},</math> and <math>r = |w|^2 \in \mathbb{R}.</math> Thus, we have <math>a^2+4a+40+r^2-12r=0,</math> and the discriminant of this must be nonnegative as <math>a</math> is real. Thus, <math>16-4(40+r^2-12r) \geq 0</math> or <math>(r-6)^2 \leq 0,</math> which forces <math>r = 6,</math> as claimed. | Let <math>a = w + \overline{w} \in \mathbb{R},</math> and <math>r = |w|^2 \in \mathbb{R}.</math> Thus, we have <math>a^2+4a+40+r^2-12r=0,</math> and the discriminant of this must be nonnegative as <math>a</math> is real. Thus, <math>16-4(40+r^2-12r) \geq 0</math> or <math>(r-6)^2 \leq 0,</math> which forces <math>r = 6,</math> as claimed. | ||
− | + | Thus, we plug in <math>z \overline{z} = 6,</math> and get: <math>72 = 4(z + \overline{z}) + 76 + (z + \overline{z})^2,</math> ie. <math>(z+\overline{z})^2 + 4(z + \overline{z}) + 4 = 0,</math> or <math>(z+\overline{z} + 2)^2 = 0,</math> which means <math>z + \overline{z} = \boxed{\textbf{(A) }-2}</math> and that's our answer since we know <math>\overline{z} = 6 / z</math> | |
− | Thus, we plug in <math>z \overline{z} = 6,</math> and get: <math>72 = 4(z + \overline{z}) + 76 + (z + \overline{z})^2,</math> ie. <math>(z+\overline{z})^2 + 4(z + \overline{z}) + 4 = 0,</math> or <math>(z+\overline{z} + 2)^2 = 0,</math> which means <math>z + \overline{z} = \boxed{-2}</math> and that's our answer since we know <math>\overline{z} = 6 / z</math> | ||
- ccx09 | - ccx09 | ||
==Solution 5== | ==Solution 5== | ||
− | Observe that all the answer choices are real. Therefore, <math>z</math> and <math>\frac{6}{z}</math> must be complex conjugates as this is the only way for both their sum (one of the answer choices) and their product (<math>6</math>) to be real. Thus <math>|z|=|\tfrac{6}{z}|=\sqrt{6}</math>. We will test all the answer choices, starting with <math>\textbf{(A)}</math>. Suppose the answer is <math>\textbf{(A)}</math>. If <math>z+\tfrac{6}{z}=-2</math> then <math>z^{2}+2z+6=0</math> and <math>z=\frac{-2\pm\sqrt{4-24}}{2}=-1\pm\sqrt{5}i</math>. Note that if <math>z=-1+\sqrt{5}i</math> works, then so does <math>-1-\sqrt{5}i</math>. It is relatively easy to see that if <math>z=-1+\sqrt{5}i</math>, then <math>12|z|^{2}=12\cdot 6=72, 2|z+2|^{2}=2|1+\sqrt{5}i|=2\cdot 6=12, |z^{2}+1|^{2}=|-3-2\sqrt{5}i|^{2}=29,</math> and <math>72=12+29+31</math>. Thus the condition <cmath>12|z|^{2}=2|z+2|^{2}+|z^{2}+1|^{2}+31</cmath> is satisfied for <math>z+\tfrac{6}{z}=-2</math>, and the answer is <math>\boxed{\textbf{(A)} | + | Observe that all the answer choices are real. Therefore, <math>z</math> and <math>\frac{6}{z}</math> must be complex conjugates as this is the only way for both their sum (one of the answer choices) and their product (<math>6</math>) to be real. Thus <math>|z|=|\tfrac{6}{z}|=\sqrt{6}</math>. We will test all the answer choices, starting with <math>\textbf{(A)}</math>. Suppose the answer is <math>\textbf{(A)}</math>. If <math>z+\tfrac{6}{z}=-2</math> then <math>z^{2}+2z+6=0</math> and <math>z=\frac{-2\pm\sqrt{4-24}}{2}=-1\pm\sqrt{5}i</math>. Note that if <math>z=-1+\sqrt{5}i</math> works, then so does <math>-1-\sqrt{5}i</math>. It is relatively easy to see that if <math>z=-1+\sqrt{5}i</math>, then <math>12|z|^{2}=12\cdot 6=72, 2|z+2|^{2}=2|1+\sqrt{5}i|=2\cdot 6=12, |z^{2}+1|^{2}=|-3-2\sqrt{5}i|^{2}=29,</math> and <math>72=12+29+31</math>. Thus the condition <cmath>12|z|^{2}=2|z+2|^{2}+|z^{2}+1|^{2}+31</cmath> is satisfied for <math>z+\tfrac{6}{z}=-2</math>, and the answer is <math>\boxed{\textbf{(A) }-2}</math>. |
+ | |||
+ | ==Solution 6== | ||
+ | Using <math>z\bar{z}=|z|^2</math>, we have | ||
+ | \begin{align*} | ||
+ | 12z\bar{z} = 2(z + 2)(\bar{z} + 2) + (z^2 + 1)(\bar{z}^2 + 1) + 31 &\implies z^2\bar{z}^2 + z^2 + \bar{z}^2 + 1 + 2z\bar{z} + 4z + 4\bar{z} + 8 + 31 - 12z\bar{z} = 0 \\ | ||
+ | &\implies z^2\bar{z}^2 - 10z\bar{z} + (z^2 + \bar{z}^2) + 4(z + \bar{z}) + 40 = 0 | ||
+ | \end{align*} | ||
+ | Let <math>p = z\bar{z}</math> and <math>s = z + \bar{z}</math>. Then we get | ||
+ | \begin{align*} | ||
+ | p^2 - 10p + s^2 - 2p + 4s + 40 = 0 \implies p^2 - 12p + s^2 + 4s + 40 = 0 | ||
+ | \end{align*} | ||
+ | Completing the square, we get | ||
+ | <cmath>(p-6)^2 - 36 + (s+2)^2 - 4 + 40 = (p-6)^2 + (s+2)^2 = 0</cmath> | ||
+ | Therefore, <math>p = 6</math> and <math>s = -2</math>. So, <math>z + \bar{z} = -2</math> and <math>z\bar{z} = 6</math>. Plugging into <math>z + \frac{6}{z}</math>, we get | ||
+ | <cmath> z + \frac{6}{z} = z + \frac{6\bar{z}}{z\bar{z}} = z + \frac{6\bar{z}}{6} = z + \bar{z} = \boxed{\textbf{(A) }-2} </cmath> | ||
+ | |||
+ | ~[https://artofproblemsolving.com/wiki/index.php/User:Crazyvideogamez CrazyVideoGamez] | ||
+ | |||
+ | ==Video Solution by OmegaLearn (Using Complex Number Identities)== | ||
+ | https://youtu.be/AEbMTTGEZV4 | ||
+ | ~pi_is_3.14 | ||
+ | |||
+ | ==Video Solution== | ||
+ | |||
+ | https://youtu.be/Yw-IJvfrT_U | ||
+ | ~MathProblemSolvingSkills.com | ||
+ | |||
+ | (includes review of complex numbers) | ||
+ | |||
+ | |||
+ | |||
==Video Solution by Punxsutawney Phil== | ==Video Solution by Punxsutawney Phil== |
Latest revision as of 11:39, 5 November 2024
Contents
Problem
Let be a complex number satisfying
What is the value of
Solution 1
Using the fact , the equation rewrites itself as
As the two quantities in the parentheses are real, both quantities must equal
so
Solution 2
Let ,
By the equation given in the problem
Therefore, and
,
,
Solution 3
Let . Then
. From the answer choices, we know that
is real and
, so
. Then we have
Plugging the above back to the original equation, we have
So
.
~Sequoia
Solution 4 (Funny Observations)
There are actually several ways to see that I present two troll ways of seeing it, and a legitimate way of checking.
Rewrite using
Symmetric in and
so if
is a sol, then so is
TROLL OBSERVATION #1: ALL THE ANSWERS ARE REAL. THUS, which means they must be conjugates and so
TROLL OBSERVATION #2: Note that because either solution must give the same answer! which means that
Alternatively, you can check:
Let and
Thus, we have
and the discriminant of this must be nonnegative as
is real. Thus,
or
which forces
as claimed.
Thus, we plug in and get:
ie.
or
which means
and that's our answer since we know
- ccx09
Solution 5
Observe that all the answer choices are real. Therefore, and
must be complex conjugates as this is the only way for both their sum (one of the answer choices) and their product (
) to be real. Thus
. We will test all the answer choices, starting with
. Suppose the answer is
. If
then
and
. Note that if
works, then so does
. It is relatively easy to see that if
, then
and
. Thus the condition
is satisfied for
, and the answer is
.
Solution 6
Using , we have
\begin{align*}
12z\bar{z} = 2(z + 2)(\bar{z} + 2) + (z^2 + 1)(\bar{z}^2 + 1) + 31 &\implies z^2\bar{z}^2 + z^2 + \bar{z}^2 + 1 + 2z\bar{z} + 4z + 4\bar{z} + 8 + 31 - 12z\bar{z} = 0 \\
&\implies z^2\bar{z}^2 - 10z\bar{z} + (z^2 + \bar{z}^2) + 4(z + \bar{z}) + 40 = 0
\end{align*}
Let
and
. Then we get
\begin{align*}
p^2 - 10p + s^2 - 2p + 4s + 40 = 0 \implies p^2 - 12p + s^2 + 4s + 40 = 0
\end{align*}
Completing the square, we get
Therefore,
and
. So,
and
. Plugging into
, we get
Video Solution by OmegaLearn (Using Complex Number Identities)
https://youtu.be/AEbMTTGEZV4 ~pi_is_3.14
Video Solution
https://youtu.be/Yw-IJvfrT_U ~MathProblemSolvingSkills.com
(includes review of complex numbers)
Video Solution by Punxsutawney Phil
See Also
2021 AMC 12B (Problems • Answer Key • Resources) | |
Preceded by Problem 17 |
Followed by Problem 19 |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 • 16 • 17 • 18 • 19 • 20 • 21 • 22 • 23 • 24 • 25 | |
All AMC 12 Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.